Changing times change translations? Reflections on the links between (r)evolution and translation - Lopes, Alexandra (2022)
This book was born from an idea and should be understood as a political gesture, in the broad sense of the word. At a time when, in academia, globalization often takes place under the aegis and almost exclusive hegemony of English, it was important for us to write a book in a language considered by many to be peripheral, despite its more than 200 million speakers around the world. (...) This volume consists of thirteen essays that reflect, in multiple ways, on the relationship between the impulse to (not) translate and the revolutionary gesture or its muzzling over time. Divided into four parts and a coda, Mudam-se os tempos, mudam-se as traduções? proposes a differentiated reflection on the relationship between translation efforts and impulses of transgression or, conversely, of preservation of the dominant taste.